Implementasi dan Tantangan Hukum Agraria dalam Sistem Hukum Nasional: Analisis Komprehensif Terhadap Aspek Regulasi, Administrasi, dan Sosial-Ekonomi - Nasywa Denada Amanda; Arrie Budhiartie; Iskandar Zulkarnain (Intellektika : Jurnal Ilmiah Mahasiswa, 2024)
This research examines in depth the implementation of agrarian law in the Indonesian national legal system with a focus on aspects of regulation, administration and socio-economic impacts. This research examines various basic problems in the implementation of the Basic Agrarian Law (UUPA), such as land conflicts, administrative systems, protection of the rights of indigenous peoples, as well as challenges in agrarian reform. The method used is normative juridical with a comprehensive socio-legal approach. The inquire about comes about appear that there's a critical crevice between the existing legitimate system and its execution within the field, particularly within the viewpoints of arrive organization, law requirement and assurance of community rights. This research identifies the need for systemic reform in national land management, modernization of the administrative system, and strengthening institutional capacity to create a more effective and just land system.